Arthritis in primary care - Atayoğlu, Ali Timuçin; Atar, Sevgi (Nova Science Publishers, Inc., 2022)
Arthritis is one of the most common conditions for visiting family physicians. Therefore, it is important to know how to diagnose and manage arthritis in primary care. Arthritis can be classified according to its duration, the number of joints involved, or whether it is inflammatory or non-inflammatory. Osteoarthritis (OA), rheumatoid arthritis (RA), ankylosing spondylitis (AS), psoriatic arthritis (PsA), and gout arthritis are among the most common arthritic diseases presented in primary care. Better outcomes may be achieved with a multidisciplinary, holistic and integrative approach.
Keywords: Holistic; Inflammatory Arthritis; Integrative; Non-Inflammatory Arthritis; Osteoarthritis; Rheumatoid Arthritis